BS EN ISO/IEC 20243-1 Information technology. Open Trusted Technology ProviderTM Standard (O-TTPS). Mitigating maliciously tainted and counterfeit products. Part 1. Requirements and recommendations (4th April 2023) - British Standards Institution,
No abstract available